(untitled) (Comprehensive Journal of Science, 2026)
The present paper attempts to study the quantitative geomorphological analysis of three main Wadis in the middle part, north of Libya namely; Wadi Zakir, Wadi Bayy and Wadi Zamzam these Wadis drain their water to Mediterranean Sea. A morphometric analysis of the studied basins has been carried out using geoprocessing techniques in GIS. This study aimed to use the Geographic Information Systems technology as an advanced means that provides accurate automated methods in extracting the morphometric characteristics of the studied basins by analyzing the digital elevation model (DEM) and building a geographical database with morphometric variables for the basins.The study showed that the areas of the basins are 7161.6 Km², 67888.9 Km² and 35923.8 Km² for Zakir, Bayy and Zamzam, respectively, which are providing a high runoff volume. The analysis of the basins reflects the following stream orders (6th order for Zakir basin, 9th order for Bayy basin and 8th order for Zamzam basin), and the dominant type of the drainage pattern of stream network in the three studied basins is the dendritic patter, which indicates the homogeneity in texture and lack of structural control. The bifurcation ratio values are (4.90 for Zakir basin, 3.75 for Bayy basin and 4 for Zamzam basin) indicating that the area is not much influenced by geological structures and undisturbed drainage patterns. The relative flood hazard degree shows that Wadi Bayy has highly flood hazard degree than Wadi Zamzam and Wadi Zakir which have moderately hazard degree